The Significance of Relations between Hungarian and Dutch Reformed Congregations under the Single-Party State – With a Special Emphasis on the Dutch Connections of Dezső Szabó, Pastor in Káloz, in the Focus of the State Security Services - KÖBEL, Szilvia (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
The study provides a glimpse into the ministry of Dezső Szabó, the Reformed pastor in Káloz (Hungary) in the 1960s, when he rebuilt informal church relations – independent of church leadership – with Dutch congregations. Prior to the war, Dezső Szabó studied in the Netherlands on a scholarship. The party-state authorities, however, did not approve of inter-church relations with Western churches, but in the changed environment of church politics and church law brought on by the 1960s, Dezső Szabó seized the opportunity to rekindle old ties through his former theological acquaintances. Dezső Szabó’s activity was monitored by state security, and the records also provide information on the situation of the Dutch Reformed Church. The study draws attention to dilemmas of wayfinding and identity, full of challenges, during the second half of the 20th century.